1970
DOI: 10.1017/s0022172400028692
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of materials used for cleaning equipment in retail food premises, and of two methods for the enumeration of bacteria on cleaned equipment and work surfaces

R. J. Gilbert

Abstract: SUIMMARYThere is no official scheme for testing disinfectants and detergent/disinfectants for use in the retail food trade and few recommended procedures have been given for the cleaning of equipment with these agents. Therefore, field trials were carried out in a large self-service store. Comparisons were made of the various cleaning efficiencies, as determined by bacterial plate counts, of detergent and disinfectant solutions and machine cleaning oils applied with either clean cloths or disposable paper towe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
2

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
2
26
2
Order By: Relevance
“…The bacteria are fixed to the wood and the efficiency of microbial recovery depends on the mechanical treatment involved. Other authors stated that recovery of bacteria by rinsing the surface is more sensitive than the recovery by agar contact plates, agar sausages and swabbing (Gilbert 1970, Kampelmacher et al 1971, Niskanen and Pohja 1977. It has been shown that destructive methods like scraping give the best bacteria recovery rates for wood and a partial revival of sublethally damaged cells takes place (Kampelmacher et al 1971, Ruosch 1981, Rödel et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria are fixed to the wood and the efficiency of microbial recovery depends on the mechanical treatment involved. Other authors stated that recovery of bacteria by rinsing the surface is more sensitive than the recovery by agar contact plates, agar sausages and swabbing (Gilbert 1970, Kampelmacher et al 1971, Niskanen and Pohja 1977. It has been shown that destructive methods like scraping give the best bacteria recovery rates for wood and a partial revival of sublethally damaged cells takes place (Kampelmacher et al 1971, Ruosch 1981, Rödel et al 1994.…”
Section: Discussionmentioning
confidence: 99%
“…Although field-tests have showed that direct swabbing techniques are superior to agar-impression methods for counting bacteria on surfaces (see Gilbert, 1970) (Gilbert & Maurer, 1968;Tebbutt, 1984). It seems that a combination of detergent activity and physical removal of bacteria are important.…”
Section: Discussionmentioning
confidence: 99%
“…Because the recovery of organisms from surfaces may be greater by a direct swabbing method than by an agar-impression technique (see Gilbert, 1970) …”
Section: Surface Cleaning and Sampling Techniquementioning
confidence: 99%
“…But they stimulated scientific work which gave microbiological reinforcement to their common sense aspects, as well as providing the technical basis for present day practice. Thus in a series of papers which took the outbreak as their starting point, Gilbert not only provided 'laboratory evidence of the obvious -that a contaminated slicing machine will easily cross-contaminate other products passed through it' (Gilbert 1969) but made evidence-based recommendations about the frequency of cleaning of food handling equipment -at least twice daily (Gilbert and Maurer 1968) -and how it could best be done -in two steps, anionic detergent cleaning followed by the application of hypochlorite (Gilbert 1970). Yet nearly 30 years later, the central Scotland outbreak showed that these simple -almost intuitively obvious -procedures had still not been universally adopted.…”
Section: Discussionmentioning
confidence: 99%